2010
DOI: 10.1097/ta.0b013e3181e03d81
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plates versus Intramedullary Nails for Fixation of Displaced Midshaft Clavicular Fractures

Abstract: Our results demonstrate no significant differences in functional outcome and nonunion rates between nails and plates fixation for displaced midshaft clavicular fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 22 publications
(49 reference statements)
6
71
2
3
Order By: Relevance
“…Irrespective of the surgical treatment (plate versus intra-medullary fixation) the studies of Ferran et al, and Liu et al, could not draw significant difference in functional outcome [17,18]. But in the aspect of complications, titanium elastic nail showed superiority over plating.…”
Section: Author's Contributionsmentioning
confidence: 92%
“…Irrespective of the surgical treatment (plate versus intra-medullary fixation) the studies of Ferran et al, and Liu et al, could not draw significant difference in functional outcome [17,18]. But in the aspect of complications, titanium elastic nail showed superiority over plating.…”
Section: Author's Contributionsmentioning
confidence: 92%
“…24,31,32,34,35 Smekal et al reported that 23% of their patients had medial nail protrusion. 24 Medial protrusion of the nail, though evident in most cases in our series, was not significant enough to necessitate removal of the hardware.…”
Section: Discussionmentioning
confidence: 99%
“…The mean time to union in our series was the same as that of Chen et al and comparable with that of conventional plating. 33,35,36,38 In a 2015 meta-analysis of plate versus intramedullary fixation of midshaft clavicle fractures, Zhang et al showed that intramedullary fixation was associated with a reduced surgery time, smaller incision, faster union rate and better shoulder function at six months. Fewer metal-ware complications and re-fracture after metal-ware removal was also noted.…”
Section: Discussionmentioning
confidence: 99%
“…10 Many studies with open nailing have demonstrated good results with less pain and early rehabilitation but none compared with the closed technique. [17][18][19][20] The results of this study show that the concept of closed reduction and internal fixation being better than open reduction and internal fixation may not hold true in case of midclavicular fractures in terms of functional outcome or time to union. But the advantage of short operative time and better cosmetic result remains.…”
Section: Discussionmentioning
confidence: 82%